Artificial Intelligence Driven Hyper-Personalization: A Systematic Review and Integrative Framework For Marketing Theory and Practice - Wahab, Agnes Chairina Putri (Journal of Marketing Breakthroughs, 2025)
Objective: This study aims to synthesize and map the development of the literature on AI-driven hyper-personalization in digital marketing, as well as to identify the intellectual framework, key research themes, and directions for future research. Research Design & Methods: This study employs a systematic literature review approach combined with bibliometric analysis. Relevant scientific articles were collected from international academic databases and analyzed using VOSviewer software to map relationships between keywords, research cluster structures, and topic development patterns in the literature. This approach enables the identification of conceptual relationships between artificial intelligence technology and the implementation of hyper-personalization in digital marketing strategies. Findings: The analysis results indicate that research on hyper-personalization is rapidly evolving and focuses on the integration of artificial intelligence, machine learning, customer data analytics, and customer experience-based marketing strategies. Keyword network visualizations indicate that artificial intelligence serves as the primary infrastructure enabling the development of more adaptive, data-driven personalization systems. Additionally, the literature emphasizes the importance of relational factors such as consumer trust, customer experience, and data privacy in determining the effectiveness of hyper-personalization implementation. Implications & Recommendations: The findings of this study underscore the importance of developing integrated data infrastructure, artificial intelligence-based analytical capabilities, and transparent data governance to support the implementation of effective hyper-personalization strategies. Future research is encouraged to develop empirical models that integrate AI capabilities, customer data integration, and relational outcomes such as engagement, trust, and loyalty. Contribution & Value Added: This study provides a comprehensive literature synthesis on AI-based hyper-personalization and offers an integrative conceptual framework linking artificial intelligence technology, data-driven marketing strategies, and customer experience in digital marketing.